GRANT OF UREA FERTILIZER AND FERTILIZER COOP COW IN IMPROVING PLANT GROWTH ALOE VERA (Aloe vera L.) - Fatimah Zahara; Darmawati J.S ,; Dafni Mawar Tarigan (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aim of this study was to determine the effect of urea fertilizer and cow manure to increase crop growth aloe (Aloe vera L.). This study was conducted in farmer group Advanced Together Hamlet IX Saentis Village, District Percut Sei Tuan, Deli Serdang implemented in the month of January 2015 until April 2015. The parameters measured were plant height (cm), number of leaves (pieces), leaf length (cm), stem diameter (mm), leaf thickness (mm), leaf weight (g) , This study uses a randomized block design factorial with two factors, ie dose of Urea (N0 = 0 g / polybag (control), N1 = 3 g / polybag, N2 = 6 g / polybag, N3 = 9 g / polybag) and Dose Manure Cows (K0 = 0 g / polybag (control), K1 = 150 g / polybag, K2 = 300 g / polybag, K3 = 450 g / polybag) treatment was repeated three times. Data were analyzed using analysis of variance followed by different test Mean according to Duncan (DMRT) at 5%. The results showed that doses of urea effect on plant height, number of leaves, leaf length, stem diameter, leaf thickness, and weight of the leaves. While cow manure on the growth of the aloe vera plant has no effect on all parameters were observed. There is no interaction between the provision of urea fertilizer and cow manure for all parameters observed.Keywords : aloe vera growth, urea, cow manure